2008
DOI: 10.1111/j.1466-7657.2007.00586.x
|View full text |Cite
|
Sign up to set email alerts
|

The SARS crisis: reflections of Hong Kong nurses

Abstract: In dealing with future health crises, it is imperative that a multilevel approach be taken.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(70 citation statements)
references
References 7 publications
6
61
0
3
Order By: Relevance
“…The fact that more than 30% of deaths due to SARS were related to the death of healthcare professionals [6] justi es this fear. Numerous studies in line with our study mentioned challenges such as nurses' fear of getting the infection and transmitting it to family members [13,[45][46][47][48][49], fear and helplessness due to the outbreak of the disease [7,8] and rapid change in recommendations and knowledge related to emerging and unknown diseases [50][51][52]. According to the results of the Cui et al, 2020 study, the most important predictor of anxiety and stress in nurses working in the COVID-19 ward was the fear of infecting family members [53].…”
Section: Discussionsupporting
confidence: 75%
“…The fact that more than 30% of deaths due to SARS were related to the death of healthcare professionals [6] justi es this fear. Numerous studies in line with our study mentioned challenges such as nurses' fear of getting the infection and transmitting it to family members [13,[45][46][47][48][49], fear and helplessness due to the outbreak of the disease [7,8] and rapid change in recommendations and knowledge related to emerging and unknown diseases [50][51][52]. According to the results of the Cui et al, 2020 study, the most important predictor of anxiety and stress in nurses working in the COVID-19 ward was the fear of infecting family members [53].…”
Section: Discussionsupporting
confidence: 75%
“…Findings revealed significant personal safety concerns driving many nurses to consider resigning from their place of employment. Heightened anxiety about the risks associated with acute care employment during pandemics has been previously reported (Holroyd & McNaught, 2008; Kang, Son, Chae, & Corte, 2018; Koh, Hegney, & Drury, 2012; Lam & Hung, 2013). Rapidly changing clinical practice, inadequate pandemic preparation, insufficient and limited resources, and potential disease exposure all contribute to perceived threats to personal safety (Holroyd & McNaught, 2008; Shiao, Koh, Lo, Lim, & Guo, 2007).…”
Section: Discussionmentioning
confidence: 83%
“…At the policy level, nine studies suggested to develop a strategic plan for future outbreaks (Sin and Huak 2004 ; Tolomiczenko et al 2005 ; Wong et al 2005 ; Lu et al 2006 ; Maunder et al 2006 ; Holroyd and McNaught 2008 ; Lung et al 2009 ; Corley et al 2010 ; Kim 2018 ) and one study to conduct public campaigns to protect HCWs and reduce their stigmatization (Matsuishi et al 2012 ). From an organizational point of view, many studies underlined how it is important to ensure favourable work conditions (Bai et al 2004 ; Maunder et al 2006 ; Su et al 2007 ; Austria-Corrales et al 2011 ; Matsuishi et al 2012 ) and provide HCWs with all the personal protective equipment (PPE) necessary to work safely and reduce their risk (Chen et al 2005a , b ; Goulia et al 2010 ; Khalid et al 2016 ).…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, it is important that the whole national health system is involved in the development of preventive strategies (Sin and Huak 2004;Tolomiczenko et al 2005;Wong et al 2005;Lu et al 2006;Maunder et al 2006;Holroyd and McNaught 2008;Lung et al 2009;Corley et al 2010;Kim 2018). Corley et al (2010) underlined the relevance to plan a strategic approach for future pandemics, through Pittsburgh sleep quality index Su et al (2007) Spielberger trait anxiety inventory Su et al (2007) effective information regarding infection control interventions, in both clinical and non-clinical settings.…”
Section: Policy-related Strategiesmentioning
confidence: 99%